2021
DOI: 10.2478/enr-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypothyroidism and autoimmune thyroiditis alter the transcriptional activity of genes regulating neurogenesis in the blood of patients

Abstract: Objective. Thyroid hormones play an important role in the development and maturation of the central nervous symptom and their failure in the prenatal period leading to an irreversible brain damage. Their effect on the brain of adult, however, has not been fully studied. With the discovery of neurogenesis in the adult brain, many recent studies have been focused on the understanding the basic mechanisms controlling this process. Many neurogenesis regulatory genes are not only transcribed but also translated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Some studies have demonstrated a significant prevalence of antibodies to the N-terminus of glutamate receptor (GluR) subunits of the N-methyl-D-aspartate (NMDA) type (GluN1-NT and GluN2B-NT2) among subjects suffering from psychiatric disorders with anti-thyroid antibodies [ 14 ]. Previously, we reported autoimmune thyroiditis (AIT) and hypothyroidism to affect transcription of the genes implicated in neurogenesis, the transmission of nerve impulses, and the regulation of the cell cycle [ 15 19 ]. In the present study, we examined the NMDA gene polymorphism (rs4880213) and the GRIN2B blood serum levels in patients with thyroid pathology in the population of Western Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated a significant prevalence of antibodies to the N-terminus of glutamate receptor (GluR) subunits of the N-methyl-D-aspartate (NMDA) type (GluN1-NT and GluN2B-NT2) among subjects suffering from psychiatric disorders with anti-thyroid antibodies [ 14 ]. Previously, we reported autoimmune thyroiditis (AIT) and hypothyroidism to affect transcription of the genes implicated in neurogenesis, the transmission of nerve impulses, and the regulation of the cell cycle [ 15 19 ]. In the present study, we examined the NMDA gene polymorphism (rs4880213) and the GRIN2B blood serum levels in patients with thyroid pathology in the population of Western Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…A significant factor involved in the induction of autoimmune response is a defect in or deficiency of the immune regulation, particularly disequilibrium between the effector T cells (Teff) and regulatory T cells (Treg) which normally prevent the development of autoimmunity (2,3). Multiple susceptibility genes may be involved in the disease development, some of which are also implicated in other autoimmune diseases (4,5), while others are specific to thyroid autoimmunity (6,7). However, data about the expression of сytokines and cytokine receptor pathway-focused genes in patients with different forms of thyroid pathology from Europe are limited, and no such data from Ukraine has been internationally published.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have proved that AIT and hypothyroidism can impair the transcription of genes engaged in neurogenesis [15], [16], the transmission https://oamjms.eu/index.php/mjms/index of nerve impulses [17], and the regulation of the cell cycle [18]. Such changes in gene expression may influence the development of neurological complications associated with thyroid pathology [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%